Women, Drug Dependency and Consequences: A Study from a Developing Country. (23rd February 2015) - Khajedaluee, Mohammad; Dadgarmoghaddam, Maliheh; Erfanian, Majidreza; Alipourtabrizi, Arash; Khadem-Rezaiyan, Majid
Abstract : Introduction . Addiction in women can expose them to malnutrition, high blood pressure, cancer, and some other dangerous diseases like hepatitis, AIDS, or other sexual transmitted diseases. The aim of this study was to assess illegal sexual relations in three groups of women. Methods . This is a cross-sectional study that was done on 236 girls and young women aged 16–25 years in 2012 in three groups: vulnerable women who have substance dependency (crimes that had made women incarcerated were considered as vulnerability in this study), invulnerable women who have substance dependency (substance dependent women without a history of incarceration), and a control group (women with no history of substance dependency or being in prison). Results . 43.8% of vulnerable women who have substance dependency had extramarital sexual relations; this percentage was 55.8% in invulnerable women who have substance dependency and 1.4% in the control group. Crystal and methamphetamine abuse was higher in addicts who had extramarital sexual relations and alcohol abuse was correlated with unsafe sexual intercourse (r =; 0.36, P = 0.001 ). There was a statistically significant difference in extramarital sexual relation based on marital status (P < 0.001 ). Conclusions . Poverty, drug dependency, divorce, and alcohol consumption make women prone to other high risk behaviors that need more attention.